Innovation norms during COVID-19 and Indonesian hotel performance: Innovative energy use as a mediating variable - Alim Syariati; Namla Elfa Syariati; Rizka Jafar; Bahrul Ulum Rusydi (Cogent Business & Management, 2023)
This study investigates the strategic effects of innovation norms-opportunity awareness and creative environment-to execute better innovative energy use and obtain better hotel performance during the COVID-19 outbreak. This exploration may shed light on the coping mechanism of hospitality business under the perspective of Resource-based Views. This study designed a survey, under the quantitative approach, to hotel managers in Makassar, Indonesia, resulting in a 204-response rate. The data was analyzed using the partial-least-square structural-equation modeling (PLS-SEM). The findings confirm the acceptance of all proposed hypotheses. Innovative norms-opportunity awareness and creative environment-are the foundation of executing energy-saving use in the organization. Finally, it mediates the relationship between innovation norms and hotel performance. This finding indicates the importance of green-innovative resources to mitigate the negative consequences of economic turbulence.
Keywords: L25; P18; P28; Z32; 650; Covid-19; Energy Use; Hotel Performance; innovation; Strategy